Inspection and testing methodology for safety instrumented system of oil and gas pipeline - Yu DIAO; Qiujuan LI; Zhaoyang LIU; Zifeng YU; Fengyin ZHANG; Dongyang LI; Shan HUANG; Ye TAO (You-qi chuyun)
Objective The flourishing construction and rapid development of smart pipeline networks and unattended stations have elevated the requirements for oil and gas pipelines and stations, particularly in terms of safety and reliability. The Safety Instrumented System (SIS) is recognized as a crucial element in ensuring the safety and reliability of oil and gas pipelines. Furthermore, inspection and testing are acknowledged as pivotal to guarantee that SIS operates at the design safety integrity level. However, there exists a lack of effective technical means to support SIS inspection and testing in China. Methods After investigating the current status of SIS inspection and testing techniques in China and abroad, and reviewing pertinent Chinese and foreign SIS standards and specifications, an SIS inspection and testing methodology was proposed for the oil and gas pipeline sector, considering field engineering practices. Additionally, an SIS inspection and testing technology system was developed, encompassing information acquisition at stations, identification of fault modes, evaluation of fault coverage, calculations of failure probabilities, and validation of safety integrity levels. This system aims to elucidate the requirements, items, and methods of SIS inspection and testing. Results The proposed methodology effectively identified three categories of functional safety risk items during on-site SIS inspection and testing: potential SIS hardware faults, misconfigurations and operational defects within the SIS, and management flaws present in the SIS operation process. The simplified calculation method introduced for inspection and testing coverage successfully verified the safety integrity level of the SIS in alignment with design requirements, considering parameters like fault coverages and cycles of the inspection and testing. These verification results were leveraged as the basis for assessing the station SIS's sustained and adequate capacity for risk reduction. Conclusion The proposed on-site SIS inspection and testing approach for oil and gas pipelines offers a valuable guide not only for the oil and gas pipeline sector but also for other industries in SIS inspection and testing. The research findings offer a reference and support to enhance the operational and maintenance capabilities of SIS at oil and gas stations, as well as to strengthen the risk management and control capabilities of pipeline enterprises.